B7-H6-mediated downregulation of NKp30 in NK cells contributes to ovarian carcinoma immune escape - Pesce, Silvia; Tabellini, Giovanna; Cantoni, Claudia; Patrizi, Ornella; Coltrini, Daniela; Rampinelli, Fabio; Matta, Jessica; Vivier, Eric; Moretta, Alessandro; Parolini, Silvia; et al. (Italian Journal of Anatomy and Embryology, 2015)
In this study the phenotype and function of tumor-associated NK cells from perito- neal fluids of a selected cohort of patients with seropapillary ovarian carcinoma were analyzed. In >50% of these patients the expression of the activating receptor NKp30 (1) in tumor-associated NK cells was substantially reduced as compared to autolo- gous peripheral blood NK cells. The impaired expression of this receptor was associ- ated with the presence of one of its cellular ligands (B7-H6) (2), which was detectable as a surface/cytosolic molecule in tumor cells and as a soluble molecule in the peri- toneal fluid. NK cells from patients expressing this NKp30low phenotype displayed an impaired IFNγ production and cytolytic function when tested against target cells expressing surface B7-H6. Our data also suggest that in these patients the defective expression and function of NKp30 may be induced by the chronic engagement of this receptor by soluble B7-H6 or by tumor cells expressing this ligand. The impairment of NK cell functions described herein could represent a novel mechanism by which the tumor microenvironment may contribute to the escape from immune surveillance. This work was supported by grants awarded by Associazione Italiana Ricerca per la Ricerca sul Cancro (AIRC)-Special Project 5x1000 no. 9962 and IG 2014 Id. 15704 (Alessandro Moretta); PRIN 2010 (Alessandro Moretta); Progetto di Ricerca Fondazione Carige 2013 (Emanuela Marcenaro); Progetto di Ricerca di Ateneo 2014 (Emanuela Marcenaro). Eric Vivier laboratory is supported by the European Research Council (THINK Advanced Grant), by Equipe Labellisée La Ligue and by institutional grants from INSERM, CNRS, and Aix-Marseille University to CIML.